Determinants encoding fimbriae type 1 in fecal Escherichia coli are associated with increased frequency of bacteriocinogeny - Štaudová, Barbora; Micenková, Lenka; Bosák, Juraj; Hrazdilová, Kristýna; Slaninková, Eva; Vrba, Martin; Ševčíková, Alena; Kohoutová, Darina; Woznicová, Vladana; Bureš, Jan; Šmajs, David (BMC microbiology, 2015)
BACKGROUND: To screen whether E. coli strains encoding type 1 fimbriae, isolated from fecal microflora, produce bacteriocins more often relative to fimA-negative E. coli strains of similar origin. METHODS: PCR assays were used to detect presence of genes encoding 30 bacteriocin determinants (23 colicin- and 7 microcin-encoding genes) and 18 virulence determinants in 579 E. coli strains of human and animal origin isolated from hospitals and animal facilities in the Czech and Slovak Republic. E. coli strains were also classified into phylogroups (A, B1, B2 and D). RESULTS: fimA-negative E. coli strains (defined as those possessing none of the 18 tested virulence determinants) were compared to fimA-positive E. coli strains (possessing fimA as the only detected virulence determinant). Strains with identified bacteriocin genes were more commonly found among fimA-positive E. coli strains (35.6%) compared to fimA-negative E. coli strains (21.9%, p<0.01) and this was true for both colicin and microcin determinants (p=0.02 and p<0.01, respectively). In addition, an increased number of strains encoding colicin E1 were found among fimA-positive E. coli strains (p<0.01). CONCLUSIONS: fimA-positive E. coli strains produced bacteriocins (colicins and microcins) more often compared to fimA-negative strains of similar origin. Since type 1 fimbriae of E. coli have been shown to mediate adhesion to epithelial host cells and help colonize the intestines, bacteriocin synthesis appears to be an additional feature of colonizing E. coli strains.
Keywords: prasata; Feces; Swine; polymerázová řetězová reakce; Slovakia; Slovenská republika; Virulence Factors; Česká republika; Sequence Analysis, DNA; sekvenční analýza DNA; Fimbriae, Bacterial; molekulární sekvence - údaje; Escherichia coli; faktory virulence; Czech Republic; Bacteriocins; bakteriociny; DNA, Bacterial; DNA bakterií; Animals; lidé; Humans; zvířata; bakteriální fimbrie; Molecular Sequence Data; Polymerase Chain Reaction; feces